Identification and functional analysis of bacteria in sclerotia of Cordyceps militaris - Luo,Li; Zhou,Jiaxi; Xu,Zhongshun; Guan,Jingqiang; Gao,Yingming; Zou,Xiao (PeerJ, 2021)
Background Cordyceps militaris is a fungus that parasitizes insects. Compounds from C. militaris are valuable in medicine and functional food. There are many kinds of bacteria in the natural sclerotia of C. militaris. However, the community structure of microorganisms in samples from different places may be different, and their corresponding ecological functions require experimental verification. Methods We used high-throughput sequencing technology to analyze bacterial 16S rRNA gene sequences in sclerotia of three samples of C. militaris from Liaoning Province, China. We isolated, identified and verified the function of culturable bacterial strains from the sclerotia. Results Pseudomonas, Pedobacter, Sphingobacterium, and Serratia were the dominant bacterial genera in the sclerotia. And function prediction showed that Pseudomonas and Pedobacter could be heterotrophic, Sphingobacterium could decompose urea, and Serratia could reduce nitrate. Two strains of bacteria isolated from the sclerotia of C. militaris, N-2 and N-26, were identified as Stenotrophomonas maltophilia and Pseudomonas baetica, respectively, based on culture and biochemical characteristics. When these isolated strains were co-cultured with C. militaris, the mycelium biomass and mycelium pellet diameter decreased, and the content of extracellular polysaccharide increased. Strain N-26 decreased the cordycepin content in C. militaris. Conclusions Bacteria in sclerotia have an important effect on the growth of C. militaris and the production of its metabolites.
Keywords: Cordyceps militaris; Microbial community; Co-culture; Functional analysis